Through the sands of time : a history of the Jewish community of St. Thomas, U.S. Virgin Islands - Cohen, Judah M. (Brandeis series in American Jewish history, culture, and life., 2004)
"In Through the Sands of Time, Judah M. Cohen offers a historical portrait of this unusual and tenacious group of Jews. Beset with frequent fires, hurricanes, earthquakes, epidemics, economic depressions, and political upheavals, the Jews of St. Thomas have survived into the twenty-first century, with their synagogue continuing to host to a Jewish religious service every week."--Jacket